Practical audio electronics - Robinson, Kevin (Routledge, an imprint of the Taylor & Francis Group, 2020)
"Practical Audio Electronics is a comprehensive introduction to basic audio electronics and the fundamentals of sound circuit building, providing the reader with the necessary knowledge and skills to undertake projects from scratch. Imparting a thorough foundation of theory alongside the practical skills needed to understand, build, modify, and test audio circuits, this book equips the reader with the tools to explore the sonic possibilities that emerge when electronics technology is applied innovatively to the making of music. Suitable for all levels of technical proficiency, this book encourages a deeper understanding through highlighted sections of advanced material and example projects including circuits to make, alter, and amplify audio, providing a snapshot of the wide range of possibilities of practical audio electronics. An ideal resource for students, hobbyists, musicians, audio professionals, and those interested in exploring the possibilities of hardware-based sound and music creation"--